Etiquette of the antibiotic decision-making process for surgical prophylaxis in Ethiopia: a triangulated ethnographic study - Alemkere, Getachew; Tegegne, Gobezie T.; Molla, Getnet Abebe; Belayneh, Alemu; Muzeyin, Hanan; Shewarega, Wendwosen; Degefaw, Yidnekachew; Melkie, Addisu; Getahun, Workineh; Tadeg, Hailu; Alemayehu, Abebe; Girma, Eshetu; et al. (Frontiers in Public Health, 2023)
Background Prophylactic antibiotics reduce surgery-associated infections and healthcare costs. While quantitative methods have been widely used to evaluate antibiotic use practices in surgical wards, they fall short of fully capturing the intricacies of antibiotic decision-making in these settings. Qualitative methods can bridge this gap by delving into the often-overlooked healthcare customs that shape antibiotic prescribing practices. Aim This study aimed to explore the etiquette of the antibiotic decision-making process of surgical prophylaxis antibiotic use at Tikur Anbessa Specialized Hospital (TASH). Methods The observational study was carried out at TASH, a teaching and referral hospital in Addis Ababa, Ethiopia, from 26 August 2021 to 1 January 2022. Overall, 21 business ward rounds, 30 medical record reviews, and 11 face-to-face interviews were performed sequentially to triangulate and cross-validate the qualitative observation. The data were collected until saturation. The data were cleaned, coded, summarized, and analyzed using the thematic analysis approach. Result Surgical antibiotic prophylaxis (SAP) discussions were infrequent during surgical ward rounds in TASH, leading to practices that deviated from established recommendations. Clear documentation differentiating SAP from other antibiotic uses was also lacking, which contributed to unjustified extended SAP use in the postoperative period. Missed SAP documentation was common for emergency surgeries, as well as initial dose timing and pre-operative metronidazole administration. Importantly, there was no standardized facility guideline or clinical protocol for SAP use. Furthermore, SAP prescriptions were often signed by junior residents and medical interns, and administration was typically handled by anesthesiologists/anesthetists at the operating theater and by nurses in the wards. This suggests a delegation of SAP decision-making from surgeons to senior residents, then to junior residents, and finally to medical interns. Moreover, there was no adequate representation from pharmacy, nursing, and other staff during ward rounds. Conclusion Deeply ingrained customs hinder evidence-based SAP decisions, leading to suboptimal practices and increased surgical site infection risks. Engaging SAP care services and implementing antimicrobial stewardship practices could optimize SAP usage and mitigate SSI risks.